Orthopedic Rehabilitation of Adult Patients with Congenital Cleft Lip and Palate with Fixed Orthopedic Structures (Clinical Observation) - Oliinyk, М.; Oliinyk, Г. (Actual Dentistry, 2025)
Relevance. Patients with congenital cleft lip and palate require long-term dental rehabilitation under the supervision of a team of specialists, and the final stage of their treatment is prosthetic rehabilitation. After qualified intervention by a surgeon, orthodontist, speech therapist, and other specialists, the final rehabilitation is performed by an orthopedic dentist. We believe that in most cases, the first stage of this process involves the manufacture of a temporary orthopedic structure, which will later be replaced with a more advanced, fixed, or combined structure. Purpose: The described clinical case presents orthopedic rehabilitation of a patient with a congenital cleft lip and palate after completion of surgical interventions. Materials and methods: Dental clinical, radiological, and photo documentation. Conclusions: The presented clinical case demonstrates the high potential of orthopedic rehabilitation of patients with congenital cleft lip and palate. The use of fixed orthopedic structures contributes to the restoration of occlusal and functional indicators, ensuring final rehabilitation, which is a crucial factor in improving the quality of life for such patients.